2017
DOI: 10.1111/1758-2229.12524
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen or formate: Alternative key players in methanogenic degradation

Abstract: Hydrogen and formate are important electron carriers in methanogenic degradation in anoxic environments such as sediments, sewage sludge digestors and biogas reactors. Especially in the terminal steps of methanogenesis, they determine the energy budgets of secondary (syntrophically) fermenting bacteria and their methanogenic partners. The literature provides considerable data on hydrogen pool sizes in such habitats, but little data exist for formate concentrations due to technical difficulties in formate deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 106 publications
1
47
0
Order By: Relevance
“…In secondary fermentations, fatty acids and alcohols that are released as products of primary fermentations are converted to compounds that can be used by methanogens, i.e., C 1 compounds, hydrogen, and acetate. The electrons released in these fermentations are transferred to methanogenic partners either as hydrogen gas or as formate at low concentrations to render these fermentations energetically feasible (2,4,(10)(11)(12)(13). For many years, hydrogen was considered the more important electron carrier, mostly because hydrogen partial pressures could easily be measured in the headspace of culture bottles or digesters.…”
Section: Importancementioning
confidence: 99%
See 2 more Smart Citations
“…In secondary fermentations, fatty acids and alcohols that are released as products of primary fermentations are converted to compounds that can be used by methanogens, i.e., C 1 compounds, hydrogen, and acetate. The electrons released in these fermentations are transferred to methanogenic partners either as hydrogen gas or as formate at low concentrations to render these fermentations energetically feasible (2,4,(10)(11)(12)(13). For many years, hydrogen was considered the more important electron carrier, mostly because hydrogen partial pressures could easily be measured in the headspace of culture bottles or digesters.…”
Section: Importancementioning
confidence: 99%
“…For many years, hydrogen was considered the more important electron carrier, mostly because hydrogen partial pressures could easily be measured in the headspace of culture bottles or digesters. Nonetheless, formate was already discussed as an alternative electron shuttle with the descriptions of the very first defined syntrophic cocultures (4,10,(12)(13)(14). Later work has shown that several secondary ("syntrophically") fermenting bacteria may release formate rather than hydrogen as an electron sink (15)(16)(17)(18)(19)(20)(21)(22), and most hydrogen-oxidizing methanogenic partners can use both hydrogen and formate as an electron source.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…However, the interspecies exchange of hydrogen and formate has been the most widely studied. Hydrogen and formate are formed by secondary fermenting bacteria to release the excess of electrons during the oxidative degradation of organic acids (Schink, 1997;McInerney et al, 2009;Stams and Plugge, 2009;Schink et al, 2017).…”
Section: Interspecies Electron Transfer (Iet)mentioning
confidence: 99%
“…Since Bryant and co-workers discovered that their cultures of Methanobacillus omelianskii did not contain one species but a syntrophic coculture of two types of microorganisms, hydrogen and formate were recognized from the very beginning as key metabolites in the electron transfer processes between the ethanol oxidizing bacterium and the methanogenic partner (Bryant et al, 1967). Since then, many syntrophic associations have been described and the debate over which compound is the main interspecies electron carrier between the diverse syntrophic associations continues (McInerney et al, 2009;Sieber et al, 2012;Morris et al, 2013;Schink et al, 2017).…”
Section: Hydrogen and Formate As Electron Carriersmentioning
confidence: 99%